Sustainable Carbon Aerogels Derived from Nanofibrillated Cellulose as High‐Performance Absorption Materials. Issue 10 (4th March 2016) - Chen, Wenshuai; Zhang, Qi; Uetani, Kojiro; Li, Qing; Lu, Ping; Cao, Jun; Wang, Qingwen; Liu, Yixing; Li, Jian; Quan, Zhichao; Zhang, Yongshi; Wang, Sifan; et al.
Abstract : Sustainable carbon aerogels with low density (≈7.8 mg cm −3 ), high porosity, high resiliency, excellent hydrophobicity, and oleophilic characteristics are synthesized by employing nanofibrillated cellulose as the precursor. The as‐prepared carbon aerogels show a remarkable capacity for the absorption of a variety of oils and organic solvents with weight gains ranging from 7422 to 22356. Under extreme conditions (e.g., at severe temperatures and in corrosive liquids), these carbon aerogels still demonstrate a superior absorption performance. Furthermore, a device based on a composite sponge with carbon sheets (generated via the disintegration of our carbon aerogels) on the surface is successfully fabricated to materialize the large‐scale and continuous separation of containments from water. This device significantly expands the practical applications of the carbon aerogels. Abstract : Creating sustainable carbon materials for the high‐efficiency absorption of oils and organic solvents is crucial for cleaning polluted water. Here, the authors show the development of carbon aerogels from nanofibrillated wood cellulose and their robust performance and stability in the removal and collection of contaminants from water.